Optimalisasi Pemberdayaan Masyarakat Melalui Pembibitan Tanaman Obat (Biofarmaka) - Salatalohy, Asiah; Nurhikmah; Marasabessy, Muh. Hidayah; Tidore, Muh Faedly (Jurnal Pengabdian Masyarakat Hutan, 2023)
This community service activity aims in general to help community members to create medicinal plant nurseries (biopharmaceuticals) as an effort to increase family income, specifically this activity aims so that after completing the activity, participants will be able to understand and be motivated in creating medicinal plant nurseries, have the knowledge in creating nurseries as well as processing and marketing medicinal plants as an effort to increase family income. In medicinal plant nurseries, the types that will be developed are red ginger (Zingiber Officinale), turmeric (Curcuma longa Linn), ginger (Curcuma xanthorrhiza), galangal (Kaemferia galangal) and Lemongrass (Cymbopogon citratus). These plants are very promising in the midst of the Covid pandemic situation since 2020. The method used in this activity is through direct demonstration plots on land around campus 4 of Khairun University with an Adult Education (POD) approach, lectures, discussions and guidance. It is hoped that this management effort will help increase community income. Key words: biopharmaceuticals, optimization, empowerment, medicinal plants